2012
DOI: 10.1007/s00268-012-1437-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment Outcomes for Anaplastic Thyroid Carcinoma: ATC Research Consortium of Japan Cohort Study of 677 Patients

Abstract: Long-term survival is possible for selected patients with ATC. To determine the treatment strategy, UICC stage (disease extent) and other prognostic factors (e.g., biologic malignancy grade) should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
231
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 236 publications
(256 citation statements)
references
References 34 publications
16
231
7
2
Order By: Relevance
“…To date, fewer than 20 cases of anaplastic transformation at the metastatic sites have been reported in the English literature [1,[4][5][6][7][8][9][10][11]. Here, we report an additional case of anaplastic transformation which developed in the pleural metastasis, combined with a literature review.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, fewer than 20 cases of anaplastic transformation at the metastatic sites have been reported in the English literature [1,[4][5][6][7][8][9][10][11]. Here, we report an additional case of anaplastic transformation which developed in the pleural metastasis, combined with a literature review.…”
Section: Introductionmentioning
confidence: 99%
“…Although anaplastic transformation rarely occurs, anaplastic carcinoma is one of the most aggressive cancers, and is responsible for more than half of the deaths attributed to thyroid cancers, with a mean survival time of 6 months after diagnosis [3]. Anaplastic transformation commonly occurs in the thyroid and metastatic regional lymph nodes, whereas occurrence at distant metastatic sites is extremely rare [4]. Among 677 cases of anaplastic thyroid carcinoma (ATC), collected from 38 registered institutions by the ATC Research Consortium of Japan (ATCCJ), only 6 cases showed anaplastic transformation at the metastatic sites (0.9 %), and these had the worst outcomes among all ATC cases [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, long-term survival is possible when patient is younger age and tumor has smaller size, localizes in thyroid parenchyma and can be completely resected by surgery. [2][3][4] Currently, it is generally accepted that ATC does not arise de novo but rather transforms or evolves from differentiated thyroid carcinoma (DTC). 5,6) ATC is commonly related with previous or concurrent thyroid disorders, including DTC.…”
Section: Introductionmentioning
confidence: 99%
“…Sugitani et al identified age and limited tumor size which is associated with higher tumor resectability as prognostic variables 24 . Liu et al reported that tumor size < 4 cm, distant spread, surgical resection, RT and residual tumor were independent factors of prognosis of ATC patients who underwent treatment 16 .…”
mentioning
confidence: 99%